Comparing Disease-Specific and Generic Quality of Life in Korean Breast Cancer Survivors Using the FACT-B and QLI: The Importance of Instrument Selection. (March 2022) - Jang, Min Kyeong; Kim, Sung Hae; Ko, Yun Hee; Han, Jeehee; Kim, Soo Yeon; Kim, Sue
Background: Quality of life (QOL) has become an important indicator for evaluating patients' symptoms and their overall satisfaction with life. Thus, examining QOL is essential for fully understanding the life satisfaction of breast cancer survivors (BCS). However, selecting the appropriate instrument for QOL measurement is challenging, and few studies have compared disease-specific and generic QOL measures and how they reflect the impact of cancer-related symptoms on QOL in BCS. We examined QOL in BCS using both disease-specific and generic instruments and compared their representation of the QOL impacts of anxiety, depression, sleep, fatigability, and posttraumatic growth. Methods: This study involved analysis of follow-up data for an exercise intervention called the BLESS (Better Life after cancer, Energy, Strength, and Support) program, which included 40 BCS treated at 1 medical center in South Korea. Their QOL was assessed using both the Functional Assessment of Cancer Therapy-Breast (FACT-B) and Quality of Life Index (QLI). Results: Both FACT-B and QLI total scores revealed that Korean BCS had low levels of QOL. Furthermore, both FACT-B and QLI total scores were significantly related to anxiety, depression, sleep, fatigability, and posttraumatic growth in the participants. Notably, multivariate regression analysis of FACT-B and QLI total scores showed different predictors for QOL: with the FACT-B, depression was the only significant predictor, while with the QLI, posttraumatic growth was the only significant predictor. Conclusion: The selection of a given QOL instrument may affect the overall findings and interpretation of the impacts of related symptoms. The FACT-B should be considered for studies of symptoms such as depression, while the QLI is more appropriate for examining overall QOL and posttraumatic growth.